The Mediating Role of Psychological Flexibility on the Relationship Between Early Maladaptive Schemas and Borderline Personality - Noori, Saeedeh; Esmaeilpour, Khalil; Nosratabadi, Touraj Hashemi (International Journal of Psychosocial Rehabilitation, 2020)
Aim and Background: The role of cognitive schemas and object relations in personality disorders has been of interest among the researchers and therapists. Yet, the mechanism of this vulnerability is not well known.The aim of the present study was to investigate the mediating role of psychological flexibility on the relationship between early maladaptive schemas and borderline personality symptoms.Methods and Materials: This was a correlational research based on structural equation modeling. Statistical population was included all students from the Tabriz University in 2018-2019 academic years. 300 students was selected by multistage cluster sampling technique. Tools was Young Schema Questionnaire–short form (YSQ-SF), Schizotypal Trait questionnaire-B form (STB), The Acceptance and Action Questionnaire (AAQ- II), Cognitive Fusion Questionnaire (CFQ), Mindfulness Attention Awareness Scale (MAAS), Engaged Living Scale (ELS). Data were analyzed using structural equation modeling (SEM).Conclusions: The research model was confirmed. So, it can be concluded that not only borderline personality symptoms was affected by bad-functioning in maladaptive schemas but also the symptoms of this disorder were aggravated by psychological inflexibility.